Effects of age and sex on middle cerebral artery blood velocity and flow pulsatility index across the adult lifespan - Alwatban, Mohammed R. (J Appl Physiol (1985), 2021)
Reduced middle cerebral artery blood velocity (MCAv) and flow pulsatility are contributors to age-related cerebrovascular disease pathogenesis. It is unknown whether the rate of changes in MCAv and flow pulsatility support the hypothesis of sex-specific trajectories with aging. Therefore, we sought to characterize the rate of changes in MCAv and flow pulsatility across the adult lifespan in females and males as well as within specified age ranges. Participant characteristics, mean arterial pressure, end-tidal carbon dioxide, unilateral MCAv, and flow pulsatility index (PI) were determined from study records compiled from three institutional sites. A total of 524 participants [18–90 yr; females 57 (17) yr, n = 319; males 50 (21) yr, n = 205] were included in the analysis. MCAv was significantly higher in females within the second (P < 0.001), fifth (P = 0.01), and sixth (P < 0.01) decades of life. Flow PI was significantly lower in females within the second decade of life (P < 0.01). Rate of MCAv decline was significantly greater in females than males (−0.39 vs. −0.26 cm s(−1)·yr, P = 0.04). Rate of flow PI rise was significantly greater in females than males (0.006 vs. 0.003 flow PI, P = 0.01). Rate of MCAv change was significantly greater in females than males in the sixth decade of life (−1.44 vs. 0.13 cm s(−1)·yr, P = 0.04). These findings indicate that sex significantly contributes to age-related differences in both MCAv and flow PI. Therefore, further investigation into cerebrovascular function within and between sexes is warranted to improve our understanding of the reported sex differences in cerebrovascular disease prevalence. NEW & NOTEWORTHY We present the largest dataset (n = 524) pooled from three institutions to study how age and sex affect middle cerebral artery blood velocity (MCAv) and flow pulsatility index (PI) across the adult lifespan. We report the rate of MCAv decline and flow PI rise is significantly greater in females compared with in males. These data suggest that sex-specific trajectories with aging and therapeutic interventions to promote healthy brain aging should consider these findings.